Improving the photoelectrochemical catalytic ability of bismuth vanadate electrodes by depositing efficient Co-catalysts. (1st February 2019) - Chen, Shan-Lung; Lin, Lu-Yin; Chen, Yu-Shiang
Abstract: Depositing effective co-catalysts with an excellent electrocatalytic ability is one of the most efficient ways to solve the serious surface charge recombination for BiVO4 as the photocatalyst toward water oxidation. Five cheap co-catalysts based on nickel, cobalt and iron were synthesized and deposited on BiVO4 electrodes using hydrothermal synthesis and electrodeposition methods. The negatively shifted onset potentials and higher photocurrent densities were obtained for the BiVO4 electrodes with co-catalyst depositions. The best photoelectrochemical performance toward catalysing water oxidation was attained for the NiOOH/BiVO4 electrode, owing to the better intrinsic properties of NiOOH and the continuous film on the BiVO4 surface to improve the connection between nanoparticles. The loading amount of NiOOH on the BiVO4 electrode was optimized by varying the photo-assisted electrodeposition times. The NiOOH/BiVO4 electrode prepared using 15 min for the photo-assisted electrodeposition showed the highest photocurrent density of 2.10 mA/cm 2 at 1.23 V versus reversible hydrogen electrode under air mass 1.5 global illumination. The BiVO4 electrode without the co-catalyst deposition only presented a photocurrent density of 0.30 mA/cm 2 measured at the same conditions. The negatively shifted onset potential, smaller charge transfer resistance and the better long-term stability were also attained for the NiOOH/BiVO4 electrode. The excellent photoelectrochemical catalytic ability for the NiOOH/BiVO4 electrode is primarily owing to the reduced surface charge recombination and the continuous film of NiOOH on the BiVO4 electrode for achieving better connection between nanoparticles. This study confirms the function of co-catalysts and provides a systematic comparison of cheap co-catalysts deposited on the promising monoclinic BiVO4 electrode on the enhancement of the photoelectrochemical catalytic performance toward water oxidation. It is also suggested that the adequate deposition amount of the co-catalyst is of the great importance for improving the catalytic ability of the co-catalyst/photocatalyst system. Graphical abstract: Image Highlights: Five cheap co-catalysts based on Ni, Co and Fe are deposited on BiVO4 electrodes. Co3 O4, CoO(OH)x, NiOOH, FeOOH and cobalt phosphate co-catalysts are synthesized. The co-catalyst/BiVO4 electrodes show small onset potential and high photocurrent. NiOOH/BiVO4 electrode shows the best photocatalytic ability for water oxidation. A photocurrent density of 2.10 mA/cm 2 at 1.23 V vs. RHE under AM1.5G is attained.